Gênese e estatuto do Factum da razão: Kant e o problema da justificação da lei moral na Analítica da razão prática pura - Silveira, Luciano Duarte da (2011)
The Factum der Vernunft (Fact of reason) is considered one of the most controversial and difficult issues in Kant´s Kritik der praktischen Vernunft (1788), specifically in its first part. Therefore, the current master´s thesis intends to be an exegetical and systematic study of Immanuel Kant´s second Critique, in a perspective which aims to establish the genesis as well as the statute of the Factum der Vernunft by means of the reconstruction of his moral foundation. The possibility of justification in moral philosophy is intimately connected by a necessary justification of the moral law properly. The Factum consists in a necessary element in order to establish the proof of the existence of an objective freedom. In this sense, we will proceed to a systematic reconstruction of Kant´s Moral Philosophy since the Kritik der reinen Vernunft (1781) and the Grundlegung zur Metaphysik der Sitten (1785), as well as other Kant´s works. We will also look for support to some representative scholars whose research regarding this theme is relevant to the delineation of possibility of a solid justification in moral philosophy